HRD Programs and Employees’ Innovative Behavior in Nepalese Organizations: Mediating Role of Psychological Empowerment - Adhikari, Yogendra (Khwopa Journal, 2023)
This study explores the relationship between HRD programs, employees' innovative behavior, and the mediating role of psychological empowerment in the Nepalese organizational context. HRD programs are crucial for improving employees' knowledge, skills, and abilities, which can lead to improved job performance and innovation. Psychological empowerment, which refers to employees' belief in their ability to control their work and make decisions, can be a critical factor in promoting innovative behavior. There were 52984 employees from banking, insurance, and hotel industry as population from which, 607 were taken as sample using disproportionate sampling method. This study has adopted a quantitative research design. It has adopted a descriptive, correlational, and explanatory research design approach. The study has used tools like exploratory factor analysis, confirmatory factor analysis, and structural equation modeling to explore, confirm, and test the relationships among the variables. This study suggests that HRD programs can influence employees' innovative behavior in both direct and indirect ways by promoting psychological empowerment as well. The findings of this study can help organizations in Nepal design and implement HRD programs that encourage innovation and creativity by promoting psychological empowerment, ultimately leading to improved organizational performance.